The Ecological Validity of The Uniform Data Set 3.0 Neuropsychological Battery in Individuals with Mild Cognitive Impairment and Dementia - Benge, Jared F. (Clin Neuropsychol, 2022)
OBJECTIVE: Ecological validity refers to the ability of neuropsychological measures to predict real world performance. Questions remain as to the ecological validity of commonly used measures, particularly regarding their relationships to global versus specific activities of daily living among those with neurodegenerative disease. We explored these issues through the lens of the Uniform Data Set 3.0 Neuropsychological battery (UDS3NB) in individuals with mild cognitive impairment and dementia. METHOD: UDS3NB and informant rated Functional Activities Questionnaire scales were evaluated from 2,253 individuals with mild cognitive impairment and dementia. Ordinal regression equations were used to explore the relationships of demographic and cognitive variables with overall and specific instrumental activities of daily living. RESULTS: Delayed recall for visual and verbal material, and performance on trail making tests were consistent predictors of global and specific functions. Specific skills (i.e. naming or figure copy) showed differential relationships with specific activities, while phonemic fluency was not related to any particular activity. CONCLUSIONS: Measures in the UDS3NB predicted activities of daily living in individuals with MCI and dementia, providing initial support for the ecological validity of these tests. Specifically, measures that tap core deficits of AD, such as delayed recall, and sequencing/shifting, are consistent predictors of performance in daily tasks.